Using Wolbachia for Dengue Control: Insights from Modelling. Issue 2 (February 2018) - Dorigatti, Ilaria; McCormack, Clare; Nedjati-Gilani, Gemma; Ferguson, Neil M.
Abstract : Dengue is the most common arboviral infection of humans, responsible for a substantial disease burden across the tropics. Traditional insecticide-based vector-control programmes have limited effectiveness, and the one licensed vaccine has a complex and imperfect efficacy profile. Strains of the bacterium Wolbachia, deliberately introduced into Aedes aegypti mosquitoes, have been shown to be able to spread to high frequencies in mosquito populations in release trials, and mosquitoes infected with these strains show markedly reduced vector competence. Thus, Wolbachia represents an exciting potential new form of biocontrol for arboviral diseases, including dengue. Here, we review how mathematical models give insight into the dynamics of the spread of Wolbachia, the potential impact of Wolbachia on dengue transmission, and we discuss the remaining challenges in evaluation and development. Trends: Wolbachia is a vertically transmitted endosymbiotic intracellular bacterium that is naturally present in about 60% of all insect species. With the goal of reducing dengue transmission, a number of strains of Wolbachia have been deliberately transinfected into Aedes aegypti . In small-scale field releases, these strains have been shown to spread to high frequencies in Aedes aegypti populations. Wolbachia offers the potential to reduce dengue transmission via two mechanisms: reduction in mosquito population density ( Wolbachia imposes a fitness cost) and reduced vector competence. Mathematical modelling has guided our understanding of the spread of Wolbachia in mosquito populations, its potential impact on dengue transmission, and field study design. City-scale studies are now underway to evaluate the effect of releasing Wolbachia -infected Aedes aegypti on dengue transmission.